The bearing capacity based on standard penetration test - Widiarso Dian Agus; Qadaryati Nurakhmi; Winarno Tri (E3S Web of Conferences)
The stability of building construction or series is not only determined by the upper circuit but the stability of the lower series in this case the foundation plays an equally important role in maintaining the stability of the structure. In planning the foundation, the bearing capacity of the soil is an important issue. This research is focused on knowing the bearing capacity value of the allowable bearing capacity formula developed by Meyerhof. This research was conducted in the Tambakharjo area and its surroundings, Semarang City, Central Java. Field data collection includes the results of the standard penetration test (SPT) and undisturbed soil samples (UDS). The N-SPT data was later used to determine the bearing capacity of the soil. The results show a positive linear relationship between N-SPT and carrying capacity, which means the higher the N-SPT, the higher the carrying capacity value. The distribution of bearing capacity at several soil depths is indicated by a zoning map of the bearing capacity of the soil. N-SPT correlation with soil physical properties (clay fraction percentage, plasticity index percentage, and activity value) was also carried out, but most of the data stations were not in accordance with normal conditions.